2022
DOI: 10.1001/jamanetworkopen.2022.42343
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of an Ensemble Model for Automated Mammography Interpretation by Artificial Intelligence

Abstract: ImportanceWith a shortfall in fellowship-trained breast radiologists, mammography screening programs are looking toward artificial intelligence (AI) to increase efficiency and diagnostic accuracy. External validation studies provide an initial assessment of how promising AI algorithms perform in different practice settings.ObjectiveTo externally validate an ensemble deep-learning model using data from a high-volume, distributed screening program of an academic health system with a diverse patient population.De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…A study evaluating a well-known, previously externally validated, high performing AI algorithm on an independent, external, diverse population found that certain patient groups had much lower performance compared to other groups and previously published performances. These issues raise concerns about unintended secondary consequences for inadequate inclusion of all patient groups in testing and validation data sets [23].…”
Section: Applications For Artificial Intelligence In Breast Imaging: ...mentioning
confidence: 99%
“…A study evaluating a well-known, previously externally validated, high performing AI algorithm on an independent, external, diverse population found that certain patient groups had much lower performance compared to other groups and previously published performances. These issues raise concerns about unintended secondary consequences for inadequate inclusion of all patient groups in testing and validation data sets [23].…”
Section: Applications For Artificial Intelligence In Breast Imaging: ...mentioning
confidence: 99%
“…The FDA has created a framework for adapting current medical device regulation for ML-based software. As the work of Hsu et al 1 show, there is a pressing need for more evaluation of these tools beyond standardized benchmark data sets, and into clinical settings that reflect real patient diversity. Moreover, there is a need to generate targeted labels to allow end users to understand for whom a tool is most appropriate.…”
Section: + Related Articlementioning
confidence: 99%
“…This type of evaluation, however, leaves out the question on how the model will behave for a population with different characteristics and images acquired using different scanners. Hsu et al, 1 following an increasing number of studies of this type, followed a different type of evaluation. They took an ensemble of ML algorithms for mammography initially developed using data from the DREAM Mammography Challenge and evaluated it on an independent large data set with different demographic and clinical characteristics.…”
mentioning
confidence: 99%
See 2 more Smart Citations